A qualitative study about college students' attitudes, knowledge and perceptions regarding sugar intake. (1st April 2021) - Prada, Marília; Godinho, Cristina A.; Garrido, Margarida V.; Rodrigues, David L.; Coelho, Inês; Lopes, Diniz
Abstract: Excessive sugar intake has been associated with multiple health conditions (e.g., higher risk for non-communicable diseases). Hence, health organizations have issued guidelines defining the maximum daily intake of free or added sugars. However, data from several countries suggests that these guidelines are rarely met, particularly by young adults. For example, almost half of Portuguese adolescents and young adults exceed the recommended sugar intake. In this work, we aim to further explore college students' attitudes, knowledge, and perceptions about sugar intake, as well as about sugar intake guidelines. A thematic analysis on data from five focus groups ( N = 40) indicated that participants reported difficulty in the comprehension of added/free sugars definition and sugar intake recommendations. Overall, attitudes toward sugar were ambivalent. Sugar was simultaneously perceived as pleasurable and needed, but also as addictive and harmful. Although aware of the potential negative health outcomes associated with excessive sugar intake, most participants did not perceive being at risk due to their youth, exercise habits, or type of diet. The few concerns expressed were mostly associated with the negative impact of high sugar intake on body image (e.g., weight gain). The main barriers to reducing sugar intake identified were environmental (e.g., time restrictions, food available at the university). Still, participants could identify several individual strategies to effectively regulate sugar intake. By identifying knowledge gaps and sources of bias related to sugar consumption, our findings are useful to inform future interventions aiming to address the problem of high sugar intake among university students.